Histopathology of chronic hepatitis C in relation to virus genotype - Simonović Jasmina; Dokić Ljubiša; Čutović Milisav; Tomanović Nada; Boričić Ivan; Prostran Milica; Nešić Zorica; Delić Dragan; Švirtlih Neda (Vojnosanitetski Pregled)
Background/aim: The natural history of hepatitis C virus (HCV) infection is variable and the factors determining the course of the illness are unclear. There are geographical variations in the distribution of different HCV genotypes, and some of them are related to the specific infection routes. Regarding our country, the dominant genotype is genotype 1b. It is unclear and still remains a question whether the distinct histopathological manifestations are related to the particular genotypes of HCV. Thus, the aim of this study was to determine whether the distinct histopathological manifestations of HCV infection might be in relation to the individual virus genotype. Methods. In this study we examined 126 patients with chronic HCV infection regarding the histopathological features, demographic data, and virus genotype. The observed groups of patients were predominantly infected with HCV genotypes 1b and 3a. Results. In this study we found that the patients infected with HCV genotype 1b had more frequently moderate or severe necroinflammatory activity of the disease, significantly higher grading score as compared with other genotypes (p < 0.0001). A higher degree of fibrosis was, also, more common in the patients infected with genotype 1b of HCV as compared with other genotypes (p < 0.05). There were no significant correlations between the necroinflammatory activity of the disease and the stage of fibrosis in 1b, 4 and mixed genotypes. Conclusion. The present data support the hypothesis that distinct genotypes of HCV are associated with the particular histopathological manifestation of the disease.